The Impact of the No Jab No Play and No Jab No Pay Legislation in Australia: A Scoping Review - Burns, Sharyn; Bhoyroo, Ranila; Leavy, Justine; Portsmouth, Linda; Millar, Lynne; Jancey, Jonine; Hendriks, Jacqueline; Saltis, Hanna; Tohotoa, Jenny; Pollard, Christina (2023)
Australia has a long history of population-based immunisation programs including legislations. This paper reports on a review of evaluations of the impact of the federal No Jab No Pay (NJNPay) and state implemented No Jab No Play (NJNPlay) legislations on childhood immunisation coverage and related parental attitudes. Five databases were searched for peer-review papers (Medline (Ovid); Scopus; PsycInfo; ProQuest; and CINAHL). Additional searches were conducted in Google Scholar and Informit (Australian databases) for grey literature. Studies were included if they evaluated the impact of the Australian NJNPay and/or NJNPlay legislations. Ten evaluations were included: nine peer-review studies and one government report. Two studies specifically evaluated NJNPlay, five evaluated NJNPay, and three evaluated both legislations. Findings show small but gradual and significant increases in full coverage and increases in catch-up vaccination after the implementation of the legislations. Full coverage was lowest for lower and higher socio-economic groups. Mandates are influential in encouraging vaccination; however, inequities may exist for lower income families who are reliant on financial incentives and the need to enrol their children in early childhood centres. Vaccine refusal and hesitancy was more evident among higher income parents while practical barriers were more likely to impact lower income families. Interventions to address access and vaccine hesitancy will support these legislations.